2022
DOI: 10.1007/s12325-022-02304-0
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Lasmiditan Across Patient and Migraine Characteristics in Japanese Patients with Migraine: A Secondary Analysis of the MONONOFU Trial

Abstract: Introduction This MONONOFU trial subgroup analysis evaluates the efficacy of lasmiditan across patient and migraine characteristics in Japanese patients with migraine. Methods MONONOFU trial was a multicenter, randomized, double-blind, placebo-controlled study. The patients were randomly assigned in a 3:7:6:7 ratio to receive lasmiditan 50 mg, 100 mg, 200 mg, or placebo for a single migraine attack within 4 h of pain onset. Efficacy of lasmiditan vs placebo was evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 34 publications
(58 reference statements)
0
3
0
Order By: Relevance
“…Some studies have reported that PTL can prevent migraine by inhibiting 5-HTR2A. 41 This study found that Nano PTL can inhibit the production of cell apoptotic factors, reduce the level of apoptosis, reduce oxidative stress, and play a protective effect on intestinal barrier of sepsis rats by up-regulating the 5-HTR2A.…”
Section: Discussionmentioning
confidence: 82%
“…Some studies have reported that PTL can prevent migraine by inhibiting 5-HTR2A. 41 This study found that Nano PTL can inhibit the production of cell apoptotic factors, reduce the level of apoptosis, reduce oxidative stress, and play a protective effect on intestinal barrier of sepsis rats by up-regulating the 5-HTR2A.…”
Section: Discussionmentioning
confidence: 82%
“…Preclinical studies have shown that lasmiditan is non-vasoconstrictive and can penetrate the blood–brain barrier to reach the central nervous system [ 94 ]. Lasmiditan has been shown to be effective in the acute treatment of migraines in randomized, double-blind, placebo-controlled clinical trials [ 95 , 96 , 97 , 98 ]. Lasmiditan works by selectively activating 5-HT 1F receptors located in the trigeminal and central nervous systems [ 94 ].…”
Section: 5-ht and Migrainementioning
confidence: 99%
“…Lasmiditan is indicated for the acute treatment of migraine attacks, specifically for the relief of moderate to severe headache pain. Clinical studies have shown that lasmiditan is effective in providing freedom from pain and the most troublesome symptoms such as nausea, photophobia, and phonophobia [ 95 , 96 , 97 , 98 ]. Common side effects of lasmiditan include dizziness, fatigue, paresthesia, and sedation, which may lead to central nervous system depression.…”
Section: 5-ht and Migrainementioning
confidence: 99%
“…26 Post-hoc analysis demonstrated that there were no significant differences in patient characteristics or migraine characteristics with regard to efficacy of the 50 mg, 100 mg, 200 mg doses and that the 200 mg dose appeared to be the most efficacious in this study population. 27…”
Section: The Mononofu Trialmentioning
confidence: 99%